2018
DOI: 10.1111/bjet.12635
|View full text |Cite
|
Sign up to set email alerts
|

A pedagogy of multiliteracies: Young children and multimodal learning with tablets

Abstract: The data reported in this paper are part of a larger case study with children from 2 to 12 years of age, that took place over 4 years. The data reported here pertains to children in the age range 4–8 years of age in Australia. The children were from low socio‐economic schools in one Australian state. The study was concerned with providing empirical evidence about learning ecologies in which teachers designed multimodal experiences to support young children to become literate in the 21st century. Using a partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 14 publications
1
70
0
12
Order By: Relevance
“…Although electronic learning has long been promoted in education (Leung, 2012;Yelland, 2018), this is the first time that online learning has been used for such a long period and on a mass scale. Our findings revealed that most kindergartens and primary schools rapidly adapted their curriculum by offering online learning to facilitate children's learning.…”
Section: Families Experienced Difficulties In Distance Learningmentioning
confidence: 99%
“…Although electronic learning has long been promoted in education (Leung, 2012;Yelland, 2018), this is the first time that online learning has been used for such a long period and on a mass scale. Our findings revealed that most kindergartens and primary schools rapidly adapted their curriculum by offering online learning to facilitate children's learning.…”
Section: Families Experienced Difficulties In Distance Learningmentioning
confidence: 99%
“…Likewise, Petersen (2015) investigated children’s agency and interactions in the use of multimodal approaches, such as the use of tablets in preschools, and emphasized that understanding children’s agency may be expanded by the use of multimodal approaches. In the same line, the studies of Yelland (2018) and Hatzigianni et al (2018) show that multimodal practices contribute to children’s creation of new contexts through collaborative, communicative and meaning-making experiences, as well as social and co-operative relations. Through digital storytelling, children can organize and express ideas in a personal and meaningful way, be aware of what has captured their interest, as well as provide and explore their points of view about a subject or experience in interaction with the other children and/or their teachers.…”
Section: Theoretical Overviewmentioning
confidence: 95%
“…This paper presents qualitative analysis of student-created IDNs centring on climate change, in particular how the year 8-10 (aged 12-15) students at two schools in Wales engaged with CCE in the YCO2 programme. Ensslin et al [15] and Yelland [16] have previously studied IDNs, respectively, as interventions to improve teenage body image and literacy; to the best of our knowledge, however, IDNs have not previously been qualitatively analysed for their efficacy as CCE. This analysis of student IDNs aims to uncover the level and type of engagement with CCE that students achieved during the workshop series, with a view to supporting them towards engaging in climate change mitigation actions both at individual and structural level.…”
Section: Introductionmentioning
confidence: 99%